Dynamic associations between opioid use and anhedonia: A longitudinal study in opioid dependence. (September 2018) - Lubman, Dan I; Garfield, Joshua BB; Gwini, Stella M; Cheetham, Ali; Cotton, Sue M; Yücel, Murat; Allen, Nicholas B
Background: Anhedonia is a commonly reported symptom among substance-dependent populations that appears to diminish with sustained abstinence. However, previous research has not determined whether anhedonia is dynamically linked to changing patterns of drug use, nor whether it predicts subsequent drug use. Aims: We aimed to test whether changes in illicit opioid use would predict changes in anhedonia, and whether increases in anhedonia would predict further opioid use. Methods: We conducted a longitudinal, observational study, with a convenience sample of 121 participants with current or past-year Diagnostic and Statistical Manual for Mental Disorders, Fourth Edition Text Revision (DSM-IV-TR) opioid dependence recruited from substance use treatment and related services and from pharmacies administering opioid substitution pharmacotherapy. Anhedonia was assessed with the Temporal Experience of Pleasure Scale and frequency of illicit opioid use was assessed using timeline follow-back interviews. Results: There was a significant within-subject effect (β=−0.015; 95% CI −0.02 to −0.01; p =0.001), indicating that participants' Temporal Experience of Pleasure Scale scores typically declined (i.e. anhedonia increased) following a month with above-average opioid use and Temporal Experience of Pleasure Scale scores rose (i.e. anhedonia reduced) following a month with below-average opioid use. However, Temporal Experience of Pleasure Scale scores did not significantly predict opioid use in the subsequent month (β=−0.04, 95% CI −0.20 to 0.12; p =0.651). Conclusions: Changes in illicit opioid use predict self-reported anhedonia, suggesting a possible causal relationship whereby anhedonia is likely to worsen with frequent drug use and diminish with prolonged abstinence. However, anhedonia does not appear to drive further drug use.